Simultaneous determination of renal function biomarkers in urine using a validated paper-based microfluidic analytical device - Rossini, Eduardo Luiz [UNESP]; Milani, Maria Izabel [UNESP]; Carrilho, Emanuel; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (Elsevier, 2018)
In this paper, we describe a validated paper-based microfluidic analytical device for the simultaneous quantification of two important biomarkers of renal function in urine. This paper platform provides an inexpensive, simple, and easy to use colorimetric method for the quantification of creatinine (CRN) and uric acid (UA) in urine samples. The microfluidic paper-based analytical device (μPAD) consists of a main channel with three identical arms, each containing a circular testing zone and a circular uptake zone. Creatinine detection is based on the Jaffé reaction, in which CRN reacts with picrate to form an orange-red product. Uric acid quantification is based on the reduction of Fe3+ to Fe2+ by UA, which is detected in a colorimetric reaction using 1,10-phenanthroline. Under optimum conditions, obtained through chemometrics, the concentrations of the analytes showed good linear correlations with the effective intensities, and the method presented satisfactory repeatability. The limits of detection and the linear ranges, respectively, were 15.7 mg L−1 and 50–600 mg L−1 for CRN and 16.5 mg L−1 and 50–500 mg L−1 for UA. There were no statistically significant differences between the results obtained using the μPAD and a chromatographic comparative method (Student's t-test at 95% confidence level).
Keywords: Creatinine; Digital image; Paper-based microfluidic analytical device (μPAD); Renal function; Uric acid; Urine